Benthic Foraminifera in Intertidal Sediments Around UNSRAT Marine Station in Likupang, North Minahasa - Jane M. Mamuaja; Markus T. Lasut; Royke M. Rampengan (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Despite their biological and ecological importance, research on foraminifera is still very limited. In recent years (from 2018 to present), interest in foraminifera studies has begun to emerge and it was shown by publication of several research articles. The study was aimed to obtain basic information on the presence of foraminifera in intertidal area around UNSRAT Marine Station in Likupang, North Minahasa. Sampling for foraminifera was conducted in five stations in front of the marine station. Sediments were collected from the upper 2 cm of sediments, brought to the laboratory, washed through 63µm sieve, and air-dried. A number of > 300 foraminifera tests were picked for identification and photographed. A total of 16 genera were found and they were grouped into three functional groups: symbiont-bearing, opportunistic, and heterotrophic foraminifera. In symbiont-bearing group, Calcarina was found present in all stations and it was followed by Baculogypsina and Amphistegina. Genus Elphidium was found to be dominant in the opportunistic group, while Quinqueloculina was the only opportunistic foraminifera that was found in all stations. The study also revealed that most of the foraminifera tests were categorized intact, meaning that their morphological features were still well preserved. Keywords: benthic foraminifera, sediments, UNSRAT, Likupang